Challenges of church planting in the book of Acts, its implications for contemporary church - Alawode, Akinyemi O. (HTS teologiese studies, 2023)
Church planting is an essential instrument in God’s hand to redeem humanity through the power of the gospel. Several church planters and locations have utilised several church planting methods at different eras. The aim of this article is to find out how it was done during the apostolic period and its significance to the body of Christ. The historical-analytical method was used to discover the scriptural foundations of church planting, patterns of church planting in the book of Acts, the challenges accompanying the pattern and its implications for the contemporary church.Contribution: Therefore, the researcher believes that all Christian missionaries, missions agencies, church planters, missiologists and pastors will have a better understanding of how best to go about the business of Church planting in contemporary times as the article concludes that the church planting pattern in the book of Acts is fundamental and strategic in propagating the gospel in the world today.